Immunohistochemical Assessment of Maspin, β-Catenin, and MMP-14 in Oral Potentially Malignant Lesions and Oral Squamous Cell Carcinoma: A Retrospective Observational Study - Oana Mihaela Condurache Hrițcu; Delia Gabriela Ciobanu Apostol; Ștefan Vasile Toader; Carmen Solcan; Daciana Elena Brănișteanu; Mihaela Paula Toader; Victor-Vlad Costan (Medicina)
Background and Objectives: Oral cancer remains a critical global health burden. Oral potentially malignant disorders (OMPDs) such as leukoplakia and oral lichen planus can precede oral squamous cell carcinoma (OSCC). Inflammation, tissue remodeling, and dysregulated signaling pathways are central to malignant transformation. This observational study aimed to evaluate the expression patterns of Maspin, β-catenin, and MMP-14 by immunohistochemistry (IHC) in oral leukoplakia, oral lichen planus, OSCC, and normal mucosa, exploring associations with lesion type, with no prognostic inferences drawn from a single timepoint. Materials and Methods: Biopsy specimens from 67 patients presenting with oral lesions (27 leukoplakia, 22 lichen planus, 18 OSCC), and 10 healthy controls were collected between January 2015 and January 2023. Inclusion criteria were age over 18 years and no other chronic illness, and a histopathologic diagnosis of oral leukoplakia, oral lichen planus or OSCC. Exclusion criteria were smokers, alcohol abuse, and prior head and neck radiotherapy, prior immunosuppressive therapy, systemic inflammatory diseases, absence of histopathological confirmation of the clinical diagnosis, and squamous cell carcinoma of the vermilion. Two pathologists independently scored staining in 10 high-power fields. Normal mucosa served as baseline. Immunohistochemical analysis was conducted using specific antibodies targeting Maspin, β-catenin, and MMP-14. Marker expression was assessed using a semi-quantitative scoring system based on staining intensity and classified into four categories: negative (−), weakly positive (+) for 1–10%, moderately positive (++) for 11–50%, and highly positive (+++) for more than 50%. Results: Maspin showed moderate (++) cytoplasmic/nuclear staining in leukoplakia and lichen planus in 78% of cases and high (+++) in OSCC and stroma in all cases. β-catenin shifted from membranous moderate positivity in 100% of OPMD cases to cytoplasmic/nuclear high positivity in all cases of OSCC. MMP-14 showed positivity (+) in 89% of OPMDs and high positivity (+++) in 100% of OSCC. Conclusions: Maspin, β-catenin, and MMP-14 exhibit distinct expression patterns across lesion types. While Maspin may reflect early tissue remodeling, β-catenin and MMP-14 changes suggest Wnt signaling activation and matrix remodeling in OSCC. Longitudinal studies are needed to establish their predictive value. This observational study refrains from prognostic claims and instead highlights biomarkers for future validation.